1999
DOI: 10.1074/jbc.274.2.703
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Spliced Variant of Smad2 Lacking Exon 3

Abstract: An alternatively spliced variant of Smad2 with a deletion of exon 3 (Smad2⌬exon3) is found in various cell types. Here, we studied the function of Smad2⌬exon3 and compared it with those of wild-type Smad2 containing exon 3 (Smad2(wt)) and Smad3. When transcriptional activity was measured using the p3TP-lux construct, Smad2⌬exon3 was more potent than Smad2(wt), and had activity similar to Smad3. Transcriptional activation of the activin-responsive element (ARE) of Mix.2 gene promoter by Smad2⌬exon3 was also sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
5
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(215 citation statements)
references
References 41 publications
(68 reference statements)
6
200
5
4
Order By: Relevance
“…In contrast to p3TP-Lux, the transcriptional activation of pAR3-Lux was not induced by Smad4-HL2, probably because the primary DNA-binding component of the ARF complex is FAST1, and the DNAbinding of Smads may only minimally contribute to the transcriptional activation of pAR3-Lux (Yagi et al 1999;Labbé et al 1998). Study of the subcellular localization of different Smad4 chimeras revealed that there was no difference in the distribution of Smad4-HL2 and Smad4-WT (our unpublished data), suggesting that the H3/4 loop does not affect the nuclear localization of Smads.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast to p3TP-Lux, the transcriptional activation of pAR3-Lux was not induced by Smad4-HL2, probably because the primary DNA-binding component of the ARF complex is FAST1, and the DNAbinding of Smads may only minimally contribute to the transcriptional activation of pAR3-Lux (Yagi et al 1999;Labbé et al 1998). Study of the subcellular localization of different Smad4 chimeras revealed that there was no difference in the distribution of Smad4-HL2 and Smad4-WT (our unpublished data), suggesting that the H3/4 loop does not affect the nuclear localization of Smads.…”
Section: Discussionmentioning
confidence: 84%
“…The Smadbinding sequence in the AP-1 sites of p3TP-Lux was used as previously described (Yingling et al 1997;Yagi et al 1999). When the whole-cell lysates of transfected COS7 cells were used, Smad4-WT did not efficiently bind to DNA, as previously described (Yagi et al 1999). In contrast, Smad4-HL2 bound to DNA efficiently, and the addition of anti-FLAG antibody led to a shift of the complex with a slower mobility, indicating that the DNA-binding complex contained Smad4-HL2 (Fig.…”
Section: Dna-binding Of Smad4-hl2mentioning
confidence: 99%
See 1 more Smart Citation
“…A protruding b-hairpin loop is responsible for direct DNA contact . Smad2 is unable to bind directly to DNA because it contains an extra exon just N-terminal of the b-hairpin loop (Dennler et al, 1998;Yagi et al, 1999). SBE-like sequences have been identi®ed in the promoters of multiple TGF-b responsive genes, including plasminogen activator inhibitor-1 (PAI-1) (Dennler et al, 1998;Luo et al, 1999), junB (Jonk et al, 1998), type VII collagen (Vindevoghel et al, 1998) and the germline immunoglobulin Ia region (Hanai et al, 1999;Pardali et al, 2000a;Zhang and Derynck, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a signi®cant number of inactivating mutations have been found in SMAD2 and SMAD4 genes in a subset of pancreas or colorectal cancers, establishing their roles as tumor suppressor genes (Hahn et al, 1996;Eppert et al, 1996;Hata et al, 1997;Shi et al, 1997;White, 1998;Kretzschmar and Massague , 1998). Recently a Smad2 transcript which lacks exon 3 has been isolated from various human cell lines (Takenoshita et al, 1998;Yagi et al, 1999) but the physiological role of this spliced protein has not been elucidated yet. Our study shows that, due to the presence of TID domain encoded by exon 3, Smad2 is unable to activate transcription through the same CAGA DNA-binding elements than Smad3.…”
mentioning
confidence: 99%